The Effect of Investment Risk and Stock Liquidity on Stock Returns - Rodho, Teresia Apliana; Nugroho, Hendrato Setiabudi (Proceedings of Universitas Muhammadiyah Yogyakarta Graduate Conference, 2023)
Investment is a commitment to sacrifice consumption in the present (sacrifice current consumption) with the aim of increasing consumption in the future, investment is always associated with returns and risks. In investing, investors cannot know with certainty the results they will get in investing. However, usually the reason people want to invest is to make a profit, even though this may not necessarily happen. The purpose of the research is to determine the effect of investment risk and stock liquidity on stock returns in the banking sub-sector listed on the Indonesia Stock Exchange (IDX). The data used in this study is secondary data obtained from the annual financial reports of banking companies listed on the Indonesia Stock Exchange for 2017 - 2021. The population in this study totaled 16 companies. and samples obtained as many as 80 financial report data. The method used in this research is descriptive statistics. Partial testing of the t test obtains proximate Investment Risk results with (beta) a negative effect on stock returns. Meanwhile, stock liquidity (Trading Volume Activity/TVA) has a positive effect on stock returns. Simultaneous test results with the F test, namely Investment Risk proxied by (beta) and Stock Liquidity (Trading Volume Activity/TVA) jointly affect stock returns.